(untitled) - Whitman, William C. (Albany, 1995)
This edition offers an authoritative overview of all types of refrigeration and air conditioning systems! The new full- color edition covers virtually every type of system from gas, to oil, to electric, to large-scale commercial systems.
Keywords: Air conditioning,Refrigeration and refrigerating machinery